The correlation between dietary patterns and the incidence of hypertension among the elderly - Muhammad Rizky Samudra; Edy Suprayitno; Hamudi Prasestiyo (Universitas 'Aisyiyah Yogyakarta, 2026)
Hypertension is a chronic health problem that commonly occurs in the elderly and is significantly influenced by daily dietary patterns. A diet high in sodium, saturated fats, and sugar can increase the risk of hypertension and exacerbate the health conditions of older adults. This study aimed to determine the correlation between dietary patterns and the incidence of hypertension among the elderly. The study employed a correlational design with a cross-sectional approach. The sample was selected using a total sampling technique, involving 50 elderly individuals with hypertension. The research instrument utilized was a Food Frequency Questionnaire (FFQ). Data were analyzed using the Spearman’s Rank test. The majority of the elderly participants exhibited poor dietary patterns, accounting for 30 individuals (60%). Furthermore, most of the participants experienced Stage II Hypertension (n=31, 62%). The Spearman’s Rank test revealed a p-value of 0.000 with a correlation coefficient of 0.538. There is a significant correlation between dietary patterns and the incidence of hypertension among the elderly. It is recommended that healthcare professionals provide regular nutritional education and counseling to the elderly and their families to promote healthier dietary habits and prevent hypertension-related complications.